A Brief Review of the Safe Management of COVID-19 Related Death and Its Control Strategies - Chng, Kay Ly; Abdullah, Nor Zamzila; Mohamad Sabir, Puteri Nurin Sabrina; Shaharin, Sharafina (IIUM Medical Journal Malaysia, 2023)
Coronavirus disease 2019 (COVID-19) is a disease caused by a virus named Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). With the increasing COVID-19 associated deaths, the infectivity and handling of the dead bodies associated with COVID-19 has become a worldwide concern in terms of spreading the infection further during handling of these bodies. As precaution, measures should be taken to contain the spread of infection while handling COVID-19 associated deaths. This review article aims to review the current management of COVID-19 associated deaths and control strategies in various countries which can guide medical examiners in handling the bodies including those with autopsy.